Kearifan Lokal Pantai Minanga sebagai Dasar Pariwisata Berkelanjutan di Kabupaten Gorontalo Utara - Rahmawaty Lamato; Sunarty Suly Eraku; Moch. Rio Pambudi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Minanga Beach is a coastal tourism destination in North Gorontalo Regency possessing natural and cultural assets that can support sustainable tourism development. The local wisdom of the community serves as a crucial asset in preserving the environment and the cultural identity of the tourism area. This study aims to identify forms of local wisdom at Minanga Beach, analyze their role in supporting sustainable tourism, and formulate guidelines for its development. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, in-depth interviews, and documentation. Research informants included traditional leaders, community figures, village officials, tourism operators, MSME actors, and visitors. Data analysis was conducted using the interactive model developed by Miles, Huberman, and Saldana. The results indicate that the local wisdom of the Minanga Beach community is manifested through the *Mandi Safar* (Safar bathing) tradition, the culture of *gotong royong* (mutual cooperation), coastal environmental conservation, and the wise utilization of natural resources. This local wisdom contributes to environmental, socio-cultural, and economic sustainability for the community. Therefore, local wisdom can serve as a foundation for sustainable tourism development at Minanga Beach.